2015
DOI: 10.1016/j.jphs.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B protects against acetaminophen hepatotoxicity by inducing Nrf2 and phase II detoxification gene expression via activation of the PI3K and PKC signaling pathways

Abstract: Acetaminophen (APAP) is used drugs worldwide for treating pain and fever. However, APAP overdose is the principal cause of acute liver failure in Western countries. Salvianolic acid B (SalB), a major water-soluble compound extracted from Radix Salvia miltiorrhiza, has well-known antioxidant and anti-inflammatory actions. We aimed to evaluate the ability of SalB to protect against APAP-induced acute hepatotoxicity by inducing nuclear factor-erythroid-2-related factor 2 (Nrf2) expression. SalB pretreatment ameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 35 publications
1
46
0
1
Order By: Relevance
“…Thus, we selected the ZnPP as an inhibitor of HO-1 to investigate the relevance between the HO-1 activation and cytoprotective actions of halophenols. The ZnPP concentration used is not always consistent in the literature including 1, 5, 10, and 20  μ M [66, 71]. By our preliminary experiment, we found that 10  μ M ZnPP exhibited the most significant inhibition on the protective effects of halophenols.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, we selected the ZnPP as an inhibitor of HO-1 to investigate the relevance between the HO-1 activation and cytoprotective actions of halophenols. The ZnPP concentration used is not always consistent in the literature including 1, 5, 10, and 20  μ M [66, 71]. By our preliminary experiment, we found that 10  μ M ZnPP exhibited the most significant inhibition on the protective effects of halophenols.…”
Section: Discussionmentioning
confidence: 64%
“…Mounting evidence from preclinical studies indicates that Nrf2 signaling activation can ameliorate SAH injury and that genetic elimination of Nrf2 aggravates SAH-induced secondary complications [59,60]. In fact, recent studies in other research areas have shown that SalB upregulates Nrf2 and HO-1 protein expression and enhances the ability of potential antioxidants [61,62]. To investigate whether the protective effect of SalB against oxidative damage is associated with Nrf2 activation, we examined the effects of SalB on the Nrf2/ARE antioxidant pathway and the regulation of antioxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Our data are consistent with earlier reports demonstrating that Sal B can activate Nrf2 pathway in several other organ systems. Among them, the liver [34,35], lung [36], brain [37], kidney [38], and vascular endothelial cells [19] have all been shown to be protected by Sal B pretreatment via up-regulating Nrf2 and its downstream phase II detoxification genes. Our data and these reports all indicated that Sal B can act as a potent activator of Nrf2 both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%